Laplace inversions applied to multi–component T2–T2 exchange experiments - Fechete, Radu; Moldovan, Daniel; Demco, Dan Eugen; Blümich, Bernhard (Diffusion Fundamentals, 2009)
Two-dimensional (2D) T2-T2 molecular exchange NMR experiments with a period of magnetization storage between the two T2 relaxation encoding periods are presented. The two-dimensional time map was inverted using a fast Laplace algorithm to obtain the T2–T2 exchange map. T2–MZ(store)–T2 2D 1H NMR spectra recorded at high and low homogeneous magnetic fields of water and oil in sand, air bubbles in water and foams, exchange of liquid / foam and liquid / saturated vapours of chloroform are presented. Uni– and bi–directional exchange was observed for bubbles in water, superficial liquid shell, and foam.